Răspuns :
x^{2} -7x-8= 0
Δ= b^2 - 4ac = 49+32 = 81
x1= (-b+ radical din Δ )/2a = (7+9)/2= 16/2= 8
x2= (-b- radical din Δ )/2a= (7-9)/2 = -2/2= -1
Δ= b^2 - 4ac = 49+32 = 81
x1= (-b+ radical din Δ )/2a = (7+9)/2= 16/2= 8
x2= (-b- radical din Δ )/2a= (7-9)/2 = -2/2= -1
x²-7x=8
x²-7x-8=0
Δ=b²-4ac =(-7)²-4*1*(-8)=49+32=81
x1,2=(-b+-√Δ)/2a=(-(-7)+-√81)/2*1=(7+-9)/2
x1=(7+9)/2=16/2=8
x2=(7-9)/2=-2/2=-1
x²-7x-8=0
Δ=b²-4ac =(-7)²-4*1*(-8)=49+32=81
x1,2=(-b+-√Δ)/2a=(-(-7)+-√81)/2*1=(7+-9)/2
x1=(7+9)/2=16/2=8
x2=(7-9)/2=-2/2=-1